2013
DOI: 10.1055/s-0033-1333870
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Foley Catheters in Live Donor Kidney Transplant Recipients on Postoperative Day 1 Does Not Increase the Incidence of Urine Leaks

Abstract: Catheterization of the urinary bladder during kidney transplantation is essential. The optimal time to remove the Foley catheter postoperatively is not universally defined. It is our practice to remove the Foley catheter on postoperative day 1 in live donor kidney transplant recipients who meet our standardized protocol criteria. We believe that early removal of Foley catheters increases patient comfort and mobility, decreases the risk of catheter associated urinary tract infections, and allows for decreased h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The study by Dantas et al also demonstrated the duration of urinary bladder catheterization as main risk factor for UTIs in posttransplant patients ( 24 ). Siskind et al found that removal of Foley catheters in live donor renal transplant recipients on postoperative day 1 decreases the risk of catheter-associated UTIs and length of hospital stay ( 7 ). It also improves patient comfort, and promotes early postoperative ambulation ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study by Dantas et al also demonstrated the duration of urinary bladder catheterization as main risk factor for UTIs in posttransplant patients ( 24 ). Siskind et al found that removal of Foley catheters in live donor renal transplant recipients on postoperative day 1 decreases the risk of catheter-associated UTIs and length of hospital stay ( 7 ). It also improves patient comfort, and promotes early postoperative ambulation ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…All aspects of pre- and postoperative care of renal transplant recipients need to be evaluated to ensure optimal patient safety and clinical outcomes. Catheterization of the urinary bladder during renal transplantation is essential because postoperative urine output measurement with Foley catheterization is essential ( 7 ). Its benefits include preparation of the bladder for anastomosis and monitoring subsequent urinary output ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, early catheter removal may also be beneficial to pancreas transplant recipients. They are routinely inserted in renal transplant to allow for close monitoring of urine production, but multiple studies have shown that patients can safely tolerate catheter removal within 48 h of surgery [ 212 , 213 , 214 , 215 ]. Meta-analyses within other surgical specialities have demonstrated decreased incidence of urinary tract infections and retention with early removal [ 216 , 217 ].…”
Section: Postoperative Eras Componentsmentioning
confidence: 99%